Foraging behavior of the Restinga Tyrannulet (Phylloscartes kronei) (Aves, Tyrannidae) - Gussoni, Carlos Otávio Araujo [UNESP]; De Oliveira Santos, Marcos César [UNESP] (My University, 2011)
This study was conducted at llha Comprida (24°20'-25°03,S; 47025,-47°55'W), São Paulo state, Brazil, in areas of restinga forest between August 2008 and July 2009. A total of 613 foraging maneuvers were observed, keeping a minimum of five minutes between each observation, with the aim of characterizing the foraging behavior of Phylloscartes kronei. This species captures prey mainly with sally-strikes on green leaves between 0,5 and 15 m above the ground. On 40 occasions, it was possible to identify the captured prey, which included Lepidoptera, Orthoptera, and two species of fruits (Clusia criuva and Temstroemia bmsiliensis). © The Neotropical Ornithological Society.
Keywords: Feeding habits; Foraging tactics; Phylloscartes kronei; Restinga Tyrannulet; Tyrannidae